Estrogen-related receptor alpha (ERRα) controls the stemness and cellular energetics of prostate cancer cells via its direct regulation of citrate metabolism and zinc transportation - Taiyang Ma; Wenjuan Xie; Zhenyu Xu; Weijie Gao; Jianfu Zhou; Yuliang Wang; Franky Leung Chan (Cell Death and Disease)
Abstract Compared to most tumors that are more glycolytic, primary prostate cancer is less glycolytic but more dependent on TCA cycle coupled with OXPHOS for its energy demand. This unique metabolic energetic feature is attributed to activation of mitochondrial m-aconitase in TCA caused by decreased cellular Zn level. Evidence suggests that a small subpopulation of cancer cells within prostate tumors, designated as prostate cancer stem cells (PCSCs), play significant roles in advanced prostate cancer progression. However, their cellular energetics status is still poorly understood. Nuclear receptor ERRα (ESRRA) is a key regulator of energy metabolism. Previous studies characterize that ERRα exhibits an upregulation in prostate cancer and can perform multiple oncogenic functions. Here, we demonstrate a novel role of ERRα in the control of stemness and energetics metabolism in PCSCs via a mechanism of combined transrepression of Zn transporter ZIP1 in reducing intracellular Zn uptake and transactivation of ACO2 (m-aconitase) in completion of TCA cycle. Results also showed that restoration of Zn accumulation by treatment with a Zn ionophore Clioquinol could significantly suppress both in vitro growth of PCSCs and also their in vivo tumorigenicity, implicating that enhanced cellular Zn uptake could be a potential therapeutic approach for targeting PCSCs in advanced prostate cancer.